Usable security in Electronic Health Record System: A review on the Saudi Arabian perspective - Samina A. Khan, Syaheerah L. Lutfi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background and objective:The electronic health record (EHR) is the fundamental building block of digital healthcare. With the increase of sensitive personal data stored in the EHR, the usability of the system and information security become important concerns. Experts are constantly developing techniques to improve security while maintaining usability. This is where usable security comes into play. More specifically, it is the prevention of unauthorized access while maintaining simplicity for the user. This review paper analyses the available evidence on security and usability of healthcare software to derive recommendations for the Saudi healthcare sector.Method:A review of the current literature was conducted using PubMed, Google Scholar, and the results were analysed.Results:Healthcare professionals work under time pressure and with limited resources. They need efficient and usable digital tools that include security measures. Lack of certainty undermines information security and ultimately compromises patient safety. There are no clear global guidelines for usable security in healthcare. Usability research in other fields suggests that such research would need to be specific to a country or a region with shared cultural and linguistic traits. Conclusion:The influence of usability in health care, and EHR security in particular, shouldbe empirically investigated in a Saudi Arabian context in future studies